Management of massive gastrointestinal haemorrhage. Issue 9 (September 2022) - O'Brien, James W.; Rogers, Matthew; Gallagher, Michelle; Rockall, Timothy
Abstract: Gastrointestinal haemorrhage (GI bleeding) is a common medical emergency, with one patient presenting every 6 minutes in the UK, or 85, 000 cases per annum. It is associated with a significant mortality rate that has remained relatively static at 10% for more than two decades. Haemorrhage is commonly categorized as upper or lower gastrointestinal in origin, but for organization of care, both groups should be regarded as one clinical entity. Rapid assessment, resuscitation and correction of coagulopathy should be undertaken, and investigation or definitive management urgently arranged. For upper GI haemorrhage, endoscopy remains the cornerstone of investigation and treatment. In lower GI haemorrhage, a more nuanced algorithm utilizing CT angiography and endoscopic evaluation is recommended. Clinicians may utilize a range of treatment modalities including endoscopic and interventional techniques to diagnose and control the source of haemorrhage, which should be tailored to the site of bleeding and pathology. Where control is not achieved the clinician should consider either repeat intervention, use of alternative haemostatic techniques or a different modality to achieve haemostasis. Surgery is rarely used as a treatment and should only be undertaken where all other measures to control haemorrhage have failed.